Dynamic investigation of traction motor bearing in a locomotive under excitation from track random geometry irregularity. Issue 1 (2nd January 2022) - Liu, Yuqing; Chen, Zaigang; Zhai, Wanming; Wang, Kaiyun
ABSTRACT: Development of railway locomotive towards high-speed and high-power has a higher requirement on traction motor bearing under the intensified wheel–rail interactions since the dynamic performance of the motor bearing will directly threaten the operation safety of the locomotives. In this paper, a locomotive-track dynamics model with traction motors is established, where a detailed dynamics model of the motor bearing is included by considering comprehensively the dynamic interactions among the major components. Besides, the complicated external and internal excitations, such as the track random geometry irregularity, the time-varying mesh stiffness, the nonlinear contact stiffness between the components of the bearing, and the variable friction coefficient are fully considered. Then, the established dynamics model is validated by comparing it with field test results. The results indicate that intensified wheel–rail interaction will deteriorate the bearing working conditions apparently, which may supply certain guidance for the design of traction motor bearings in a locomotive.